Study of Codicology and Textology Manuscript of the Mushaf Al-Qur'ān Collection of K.H. TB. Lathifoedin Majalengka - Abdul Rosyid; Istikomah Nurul Hasanah (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2026)
Abstract This study examines the characteristics of a Qur'anic manuscript collection owned by K.H. T.B. Lathifoedin in Majalengka through historical, codicological, and textological perspectives. This manuscript represents an ancient document that has not yet been thoroughly studied. The lack of academic attention to the diversity of Qur'anic manuscripts in the Indonesian archipelago has resulted in many important manuscripts, such as this one, being underutilized as sources of knowledge. Therefore, the study of this manuscript is considered urgent in order to preserve historical data and safeguard the richness of Islamic cultural heritage, particularly in West Java. This research employs a qualitative method by combining a field study of the original manuscript with library research using a descriptive-comparative analysis approach. The findings reveal that, from a codicological perspective, the manuscript uses daluang paper as its medium and features naskhī, pharisa, and sulus scripts, although it lacks illumination and a colophon. From a textological perspective, the manuscript demonstrates a mixed rasm style dominated by imlā'ī elements, along with distinctive ḍabṭ features and waqf marks that differ from those found in modern standard Qur'anic texts. These findings confirm that the Qur'anic manuscript of K.H. T.B. Lathifoedin possesses unique characteristics that enrich the tradition of Qur'anic manuscript copying in the Indonesian archipelago. This study contributes significantly to the field of 'Ulūm al-Qur'ān and serves as an important reference for codicological studies of religious manuscripts in Indonesia. Abstrak Penelitian ini mengkaji karakteristik mushaf Al-Qur’an koleksi K.H. TB. Lathifoedin di Majalengka melalui tinjauan sejarah, kodikologi, dan tekstologi. Mushaf koleksi K.H. TB. Lathifoedin merupakan naskah kuno yang hingga kini belum pernah dikaji secara mendalam. Minimnya perhatian akademisi terhadap variasi mushaf Nusantara menyebabkan banyak naskah penting seperti ini belum dimanfaatkan secara optimal sebagai sumber pengetahuan. Pengkajian terhadap naskah ini menjadi sangat mendesak guna menyelamatkan data sejarah serta melestarikan kekayaan warisan budaya Islam, khususnya di Jawa Barat. Metode kajian yang digunakan adalah kualitatif dengan menggabungkan studi lapangan pada manuskrip asli dan studi pustaka melalui analisis deskriptif-komparatif. Hasil penelitian menunjukkan bahwa secara kodikologis, mushaf ini menggunakan media kertas daluang dengan tipografi khat naskhi, farisi, dan sulus, namun tidak memiliki iluminasi maupun kolofon. Secara tekstologis, naskah ini menampilkan penggunaan rasm campuran yang didominasi unsur imlā’ī, lengkap dengan karakteristik ḍabṭ serta tanda waqaf yang berbeda dari standar mushaf modern. Temuan ini menegaskan bahwa mushaf K.H. TB. Lathifoedin memiliki kekhasan yang memperkaya khazanah tradisi penyalinan Al-Qur'an di Nusantara. Penelitian ini memberikan kontribusi signifikan bagi bidang ‘Ulūm al-Qur’ān serta menjadi referensi penting dalam studi kodikologi naskah keagamaan di Indonesia.